Circuit Training Intervention for Adaptive Physical Activity to Improve Cardiorespiratory Fitness, Leg Muscle Strength Static and Balance of Intellectually Disabled Children - Sumaryanti; Tomoliyus; Japhet Ndayisenga (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2019)
Physical activity intervention programmes have been found to effectively improve cardiorespiratory fitness, strength, and balance. However, few studies thus far have examined the effects of a circuit training physical activity adaptive programmed to improve the cardiorespiratory fitness, leg muscle strength and balance of the static environment of children with intellectual disabilities. The purpose of this study was to examine the effects of the adaptive activity circuit training of six weeks performed three times per week on the cardiorespiratory fitness (VO2 max), leg muscle strength, and balance of intellectually disabled children. The research method was experimental with group pretest-posttest design. The subject of this study was 15 male students with mild intellectual disabilities aged from 15 to 17 years who followed sport extracurricular activities taken by random sampling. The cardiorespiratory fitness (VO2 max) measurement used the modified Queen's College Step Test; leg muscle strength was measured using a leg dynamometer; static balance was measured using a stork stand test. The data were analysed with a paired samples test using SPSS. The results showed significantly increased (p<0.05) cardiorespiratory fitness, leg muscle strength, and static balance at the end of the intervention period of the circuit training physical activity adaptive programme. It has been concluded that the circuit training physical activity adaptive programme of six weeks, at a frequency of three times per week was effective for improving cardiorespiratory fitness (VO2 max), leg muscle, strength and balance.